Prospects for humanity: the strategy of sufficient development by Vodopianov - Danilov, Alexander N. (Journal of the Belarusian State University. Sociology, 2023)
The article considers a complex of modern problems that pose a threat to the future of mankind. It is noted that the beginning of the 21st century in the world is characterised by global instability, new challenges and risks. There is a decrease in the activity of environmental protests, continued environmental pollution, exponential population growth, depletion of natural resources and lack of living space, the emergence of previously unknown diseases such as COVID-19, increase of inequality and the gap between the poor and the rich, etc. The arms race has resumed again, models of new equipment are created on a fundamentally new technological basis, which do not always take into account environmental consequences, the struggle for resources to the detriment of the environment is intensifying. The strategy of sufficient development proposed by the philosopher P. A. Vodopianov in the new monograph «At the turn of the era: choosing a strategy for creating the future» (2023) is analysed. In this book the paths of a new vector of socio-economic prospects are outlined basing on its coordination with the laws of evolution of the biosphere, the laws of conservation of natural ecosystems and the biosphere as a whole are revealed, and the expediency of developing environ- mentally friendly technologies and establishing of a new humanism as a necessary condition for achieving a safe future is indicated.